Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.4 - Adding and Subtracting Rational Expressions with Different Denominators - Exercise Set - Page 517: 64



Work Step by Step

$\frac{2z^2}{4z-1} - \frac{z-2z^2}{4z-1} = \frac{2z^2-(z-2z^2)}{4z-1} = \frac{2z^2-z+ 2z^2}{4z-1} = \frac{4z^2-z}{4z-1} = \frac{z(4z-1)}{4z-1} = z$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.